Unpredictable robots elicit responsibility attributions. (5th April 2023) - Franklin, Matija; Awad, Edmond; Ashton, Hal; Lagnado, David
Abstract: Do people hold robots responsible for their actions? While Clark and Fischer present a useful framework for interpreting social robots, we argue that they fail to account for people's willingness to assign responsibility to robots in certain contexts, such as when a robot performs actions not predictable by its user or programmer.